Gudbilledlighed og syndefald: Aspekter af Grundtvigs og Kierkegaards menneskesyn på baggrund af Irenæus - Cappelørn, Niels Jørgen (Grundtvig-Studier, 2004)
Gudbilledlighed og syndefald. - Aspekter af Grundtvigs og Kierkegaards menneskesyn på baggrund af Irenæus. [The Image and Likeness of God and the Fall of the Human Being. - Aspects of Grundtvig’s and Kierkegaard’s Conceptions of the Human Being in light of Irenaeus] By Niels Jørgen Cappelørn In his account of the human being, the early church father Irenaeus, the bishop of Lyon (in the second century, C.E.), makes a distinction between imago dei and similitudo dei based on the Genesis account of the creation of human beings in the image and likeness of God (Gen 1:26-27). It is the thesis of this article that this distinction can be traced in the works of N. F. S. Grundtvig and Soren Kierkegaard and that this distinction opens possibilities for finding and demonstrating new and parallel elements in Grundvig’s and Kierkegaard’s respective conceptions of the human person, particularly concerning the relationship between the image and likeness of God in human beings and the Fall. Grundtvig studied Irenaeus for the first time in 1823 and produced a translation of the fifth and final book of his apologetic work, Adversus haereses, in 1827. Kierkegaard seems not to have studied Irenaeus’ own texts, but a good ten years after Grundtvig’s translation he read about the theology of Irenaeus in Johannes Adam Mohler’s Athanasius der Große und die Kirche seiner Zeit from 1827. Irenaeus’ conception of the human being with regard to both the Fall and the rebirth in Christ can be summarized as follows: The human being consists of body and soul, which is its substance, and this substance must become united with the Spirit of God if the individual is to become a complete spiritual person. What was lost in Adam is won in Christ. But not all was lost with the Fall. The image of God is still within the human soul while the likeness of God, which resides in the human spirit, has been lost and must be reborn of the Holy Spirit. The image of God in the soul is freedom, and this remains with human beings. At times, this freedom assents to the flesh and falls into earthly desire, at times it follows the will of God and submits to His Spirit, which is granted anew in Christ. The account here of Grundtvig’s conception of the human being - specifically with regard to the consequences of the Fall for the image and likeness of God that was endowed to human beings at creation – is based on Den christelige Børnelærdom, [Elementary Christian Doctrine], which was first published in a series of articles in 1855-61 and which was later republished in book form in 1868. Additionally, it is based on a series of hymns and spiritual songs from the same period, especially “Hvor skal jeg Guds Billed finde?” [Where Shall I God’s Image Find?] and “I Begyndelsen var Ordet / Gjenlyds-Ordet i vort Bryst,” [In the Beginning Was the Word / The Resonating Word in Our Breast] together with a sermon from 1839 on Mark 7: 31-37, and finally, ‘Christenhedens Syvstjeme’ [The Pleiades of Christendom] (1854-55). The corresponding account of Kierkegaard’s conception is based on several sources: The Concept of Anxiety (1844) where the author engages in a critical rejection of the Augustinian-Lutheran understanding of inherited sin; “An Occasional Discourse” and “What We Learn from the Lilies in the Field and the Birds of the Air” from Upbuilding Discouses in Various Spirits (1847); and his discourses for Friday Communion in Christian Discourses (1848), in Three Discourses at Communion on Fridays. The High Priest - The Tax Collector - The Woman Who Sinned (1849) and in Two Discourses at the Communion on Friday (1851). Additionally, a series of other texts is consulted, including passages from Philosophical Fragments (1844) and Journals EE (1839) and HH ( 840-41). These two respective accounts reveal that the thesis of the article cannot be comprehensively applied in every detail and for every text; the constmction is too schematic and static to do justice to Gmndtvig’s dynamics and Kierkegaard’s dialectics. But as a backdrop to a reading and comparison of their respective conceptions of the human being with regard to the Fall and its consequences for the image and likeness of God in human beings, it has been helpful to treat essential aspects of their respective anthropologies. Both Gmndtvig and Kierkegaard agree with Irenaeus that human beings consist of a triad: body, soul and spirit. And they share the conviction that human beings possess an original divine stamp, established in creation, in the form of the image and likeness of God. This stamp has not completely perished with regard to the image of God, but with regard to the likeness of God, it has been lost – though Grundtvig and Kierkegaard do not make the distinction between imago dei and similitudo dei as sharply. In Grundtvig, one finds first and foremost that despite the Fall, a positive element of God’s image survives in the soul as “the resonating word” which can both hear and utter God’s creative Word. In Kierkegaard, one finds first and foremost that because of the Fall a negative element of God’s image is left behind as a cracked and split freedom which is, however, manifest positively as a consciousness of sin and a desire for God. For both of them - insofar as Irenaeus’ distinction can be sustained - a remnant of God’s image in the soul remains while the likeness of God in the spirit has been lost. They likewise agree that God’s Spirit is the driving force for both the renewal and reunification of the image and likeness of God. For Grundtvig, this renewal of the image of God and the rebirth of the likeness of God takes place through the Holy Spirit in Baptism. For Kierkegaard, where Baptism does not have the same signifying meaning, it takes place in the interaction between Confession and Communion. Grundtvig maintains a clear axis between Baptism and Communion, with an emphasis on Baptism as the place where human “sin-guilt,” which is a consequence of the Fall, is forgiven and erased once and for all. By contrast, Kierkegaard inserts a third element, Confession, so that the schema appears as follows: Baptism, Confession, Communion, but with an emphasis on Confession as the place where human beings confess their sins and God grants His forgiveness. Grundvig underscores first and foremost that Baptism is a spiritual bath of rebirth and, secondly, that it is a covenant. To be sure, they are in agreement that Baptism must be appropriated in faith but Kierkegaard, more than Grundtvig, insists that human beings constantly fall away from and break the covenant. It is here that the confessee’s admission of sin and the absolved one’s reception of God’s forgiveness in Confession receives decisive significance as a preparation to and precondition for going to Communion worthily and for accepting forgiveness at the Lord’s table. In neither of them is there a mention of a “creation anew” in the form of a second creatio ex nihilo (creation from nothing) - at least not as the dominant theme - but rather a renewal, a rebirth, a redemption, a restoration, a repetition, and a reunification in spirit and truth. While Grundtvig, who thinks especially dynamically and metaphorically, places emphasis on the homogeneous quality of the states before and after the Fall or, more specifically, before and after renewal and rebirth, Kierkegaard - who thinks more dialectically and conceptually - points to the heterogeneous quality. For both of them, one can speak of a growth: in Grundtvig, a growth in faith, hope and charity; in Kierkegaard, a growth in faith and especially in following Christ as truth which brings about a sanctifying fellowship of love and suffering in Christ.